Mn2+‐Doped CsPbI3 Nanocrystals for Perovskite Light‐Emitting Diodes with High Luminance and Improved Device Stability - Menglong Liu (Wiley-VCH, 2021)
Cubic α‐CsPbI3 has promising applications in the optoelectronic field for its excellent properties. However, α‐CsPbI3 black phase is instable at room temperature and easily converts into nonluminescent yellow orthorhombic phase (δ‐CsPbI3). Herein, the stability of α‐CsPbI3 is significantly improved by incorporating Mn2+ dopants into the perovskite lattice. Mn2+: CsPbI3 has essentially the same crystal structure as the parent α‐CsPbI3, and Mn2+ doping can promote photoluminescence quantum yield (PLQY) from 55% to 93%. Importantly, Mn2+: CsPbI3 can maintain 60% PLQY after exposing in air for 45 days, whereas the undoped CsPbI3 completely loses its luminescence in 10 days. First‐principles calculations testify that improved stability and optical properties of Mn2+: CsPbI3 are primarily attributed to the increased formation energy and tolerance factor. Accordingly, the luminance, external quantum efficiency (EQE), and T 50 lifetime of Mn2+: CsPbI3 perovskite light‐emitting diode (PeLED) reach 1066 cd m−2, 1.8%, and 2500 s, whereas the values for the undoped counterpart are only 415 cd m−2, 0.6%, and 140 s, respectively. In addition, it is evidenced that introducing a LiF buffer layer between hole transport layer and perovskite emissive layer can further boost the device performance, particularly, the luminance and T 50 lifetime achieve 1394 cd m−2 and 225 min at 140 cd m−2.